Textbook oncologic outcomes in colorectal cancer surgery: a systematic review - Arrighini, Giang Son; Martinino, Alessandro; Zecchin Ferrara, Victoria; Lorenzon, Laura; Giovinazzo, Francesco (Frontiers in Oncology, 2025)
IntroductionThe concept of “textbook outcome” has been updated to encompass the principles of surgical oncology and the related outcomes [textbook oncologic outcome (TOO)]. This systematic review aims to synthesize the numerous definitions of TOO in the context of colorectal surgery. The goal is to promote the development of a definition that has universal recognition and worldwide acceptability, hence improving surgical quality standards and patient outcomes.MethodsA systematic literature review was conducted using PRISMA guidelines. The databases PubMed, Web of Science, and Scopus were searched for studies that addressed TOO in colorectal cancer surgeries. The database search was conducted on 30 April 2024, and the primary study’s quality was assessed using the Newcastle–Ottawa Scale.ResultsA total of 13 studies were included. Common TOO parameters included radical resection, lymph node (LN) yield ≥12, no Clavien-Dindo grade ≥III complications, length of stay (75th percentile), no 30-day readmissions, and no 30-day mortality. Factors influencing TOO achievement included surgical risk, gender, tumor stage, and socioeconomic factors. Patients achieving TOO showed better long-term survival. Variability in TOO definitions highlighted the need for standardization.ConclusionTOO is an effective indicator for evaluating the quality of colorectal cancer surgery. It provides a comprehensive evaluation of surgical outcomes, which helps in guiding patient decisions and measuring hospital performance. By standardizing the parameters of TOO, the consistency and quality of care across different institutions can be improved. We propose a unified definition of TOO for colorectal cancer surgery: radical resection, LN yield ≥12, no Clavien-Dindo grade ≥III complications, length of stay (75th percentile), no 30-day readmissions, and no 30-day mortality.